Conversations with Kentucky writers II - Beattie, L. Elisabeth, 1953-; Lippman, Susan (Kentucky remembered., 2000)
In this sequel to Conversations with Kentucky Writers, L. Elisabeth Beattie brings together in-depth interviews with sixteen of the state's premiere wordsmiths. This new volume offers the perspectives of poets, journalists, and scholars as they discuss their views on creativity, the teaching of writing, and the importance of Kentucky in their work. They talk frankly about how and why they do what they do. The writers speak for themselves, and their thoughts come alive on the page. Beattie's interviews reveal the allegiances and alliances among Kentucky writers that have shaped literary trends.